An Ecolinguistic Study on Ecospiritual Tourism of Rebo Buntung Commoddification - Diah Supatmiwati; Wiya Suktiningsih; Sutarman Sutarman; Zainudin Abdussamad; Abdul Muhid (Bina Nusantara University, 2021)
The research examined the relationship between cultural ritual, linguistic, and ecology in the context of ecotourism. It aimed to encourage, stimulate, and integrate the use of religious tradition’s terms in understanding and reinterpreting the environment and human relations and its roles. Cultural forms and elements basically had the potential to be used as a tourism commodity, meaning that they could be commodified. The research also related to ecolinguistics, a study that discussed language associated with the environment in which the language grew and developed and how it was used by the community. Cultural rituals as a tourism commodity could be a means of maintaining culture and language even though they were commodified for tourism purposes. Thus, the religious-cultural structure of Rebo Buntung and Tetulaq Tamperan should be packaged following its original structure as a medium for cultural and language preservation but also packaged as attractively as possible with a contextual structure that adapted to tourism sites so that could attract tourists. This ecospiritual commodification was expected to be able to budge the economy of the surrounding community. The research was conducted at Ketapang Beach, Tanjung Menangis, Pringgabaya district, and East Lombok where Rebo Buntung ritual was carried out. The research applied a qualitative descriptive method. For this reason, the data obtained were analyzed using qualitative descriptive analysis by describing the data obtained from an informant. On that basis, it can be concluded that the practice of ecospriritual commodification can have multiple effects, not only to preserve culture and language but also to maintain community harmony with nature, as well as improve the economy of the local community.